Evaluation of Plant Growth-Promoting and Salinity Ameliorating Potential of Halophilic Bacteria Isolated From Saline Soil - Kapadia, Chintan; Patel, Nafisa; Rana, Ankita; Vaidya, Harihar; Alfarraj, Saleh; Ansari, Mohammad Javed; Gafur, Abdul; Poczai, Peter; Sayyed, R. Z. (Frontiers in Plant Science, 2022)
Among the biotic and abiotic stress affecting the physical, chemical, and biological properties of soil, Salinity is a major threat that leads to the desertification of cultivable land throughout the world. The existence of diverse and versatile microbial populations inhabiting the nutrient-rich soil and varied soil conditions affects the soil dynamism. A normal soil constitutes 600 million bacteria belonging to about 20,000 species, reduced to 1 million with 5000-8000 species in stress conditions. Plant growth-promoting rhizobacteria (PGPR) are in symbiotic association with the plant system, which helps in combating the abiotic stress and increases overall productivity and yield. These microorganisms are actively associated with varied cellular communication processes through quorum sensing and secondary metabolites such as the production of Indole-3-acetic acid (IAA), and exopolysaccharide (EPS) siderophore, ammonia, ACC deaminase, and P solubilization. The present study focused on the isolation, identification, and characterization of the microorganisms isolated from the seacoast of Dandi, Navsari. Twelve isolates manifested high salt tolerance characterized by PGPR traits at a 15 to 20 % higher salt concentration. AD9 isolate identified as Bacillus halotolerant showed a higher ammonia production (88 μg/mL), phosphate solubilization (86 μg/mL), and AD32* (Bacillus sp. clone ADCNO gave 42.67 μg/mL for IAA production. AD2 (Streptomyces sp. clone ADCNB) and AD26 (Achromobacter sp. clone ADCNI showed a high ACC deaminase activity. AD32 (Bacillus sp. clone ADCNL) gave a high siderophore activity of 65.40±1.65. These isolates produced salinity ameliorating traits, total antioxidant activities, and antioxidant enzymes namely superoxide dismutase (SOD), Glutathione oxidase (GSH), and catalase (CAT). Inoculation of the multipotent isolate that produced PGP traits and salinity ameliorating metabolites promoted the plant growth and development in rice under salinity stress conditions.